595 Outcomes of Two-Stage Revision Surgery of Oncology Endoprostheses for Prosthetic Joint Infection. (19th August 2022) - Adlan, A; McCulloch, R; Evans, S; Parry, M; Stevenson, J; Jeys, L
Abstract: Aim: We aim to report the outcomes of two-stage revision surgery to eradicate periprosthetic joint infection (PJI) of endoprostheses in orthopaedic oncology. Method: A retrospective review of 44 patients who underwent two-stage revision surgery to eradicate PJI between 1999 and 2018 was conducted at a single tertiary orthopaedic oncology centre. The patients mean age was 36.1 years (12–78). The sites of prostheses were distal femur in 50%, proximal femur in 11.4%, proximal tibia in 36.4% and total femur with proximal tibia replacement in 2%. The mean follow-up period was 6.9 years (range 0.4–19 years). Results: The overall rate of infection eradication for the patients was 95.2% at 2 years (95% CI 89–100%) and 79% (95% CI 67–93%) at 5 years. Amputation free survival was over 100% at 2 years and 88% at 5 years (95% CI 78–99.8%). There was no difference in the incidence of reinfection recurrence and amputation of patients with silver-coated implants. Coagulase-negative staphylococcus was the most common microorganism, isolated in 21 patients. Infection was successfully eradicated in 54.5%. Polymicrobial infection was recorded in 18%. Multi-drug resistance (MDR) organisms were recorded in 48% of the cohort. Conclusions: MDR and polymicrobial organisms are common in orthopaedic oncological patients with lower infection clearance rates than the primary arthroplasty group. The increased attempts at limb salvage to treat infection may explain lower infection-free survival compared to previous series at the same centre, which reported higher rates of primary amputation to treat infection as their initial management.